Modernization in the Periphery: The Introduction of the Tractor in Chile, 1910-1935 - Robles-Ortiz, C (Agricultural History Society, 2020)
This is the first study of the introduction of the tractor in a Latin American country before 1930. Challenging conventional views on agricultural mechanization in Chile, the article shows that a progressive sector of upper-class landowners and state experts introduced tractors, primarily as a solution to poor plowing and low land productivity. The first tractors were tested in 1907, starting a process of technological innovation that resulted in the adoption of tractors after World War I. Introducing the tractor into the large estates of a peripheral rural society was a learning process for Chilean agriculturalists. The first “mammoth” steam tractors proved unsuitable for Chile s farming practices, but, as US manufacturers produced more efficient models and local distributors successfully marketed them, landowners learned about their advantages. In the 1920s they adopted light, wheeled models that spread throughout Chile in the 1930s. The tractor was the culmination of a long process of mechanization of the Chilean hacienda system that developed from the 1850s. It was also a technological innovation that contributed to the drastic increase of cultivated land in Chile, and one of the sources of economic growth in Chilean agriculture in the early twentieth century. © the Agricultural History Society, 2020